Dynamics of mutal relations Lithuania and Czechoslovakia (1918-1939): new approach in history of Lithuania's diplomacy (About a Defence of Dalia Bukelevičiūtė Doctoral Thesis) - Sandra Grigaravičiūtė (Lietuvos Istorijos Studijos)
-